Pengaruh Citra Merek, Kualitas Produk, Gaya Hidup, dan Persepsi Harga terhadap Keputusan Pembelian dengan Kepuasan Konsumen sebagai Variabel Mediasi pada Konsumen Starbucks di Kota PalangkaRaya - Wika Tri Lestari; Rensa Rensa; Riska Pania Putri; Indra Saputra; Apriani Apriani; Erina Mateluni; Sri Wahyu Utami (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to examine the influence of brand image, product quality, lifestyle, and price perception on purchase decisions, with customer satisfaction as a mediating variable among Starbucks consumers in Palangka Raya City. The variables studied include brand image, product quality, lifestyle, price perception, customer satisfaction, and purchase decision, to assess both the direct and indirect effects of the four independent variables on purchase decisions through customer satisfaction. This research employs a quantitative approach with Partial Least Square (PLS) analysis using SmartPLS 3.0 software. The population consists of all Starbucks consumers in Palangka Raya, with purposive sampling techniques and a total of 100 respondents. The results show that brand image, product quality, lifestyle, and price perception have a positive and significant effect on both customer satisfaction and purchase decisions. Moreover, customer satisfaction significantly mediates the relationship between these four variables and purchase decisions. These findings indicate that efforts to enhance customer satisfaction can strengthen the impact of marketing elements on purchasing decisions among urban consumers.